The University as a Business
143 p. 10 illus.
Keywords: Worldwide, universities have recently been the object of large reform processes, facing strong pressure not only from their institutional environment to offer new programs and to adopt new governance and management systems to keep up with the growing competition in the higher education sector but also because of calls for an increase in the efficiency and effectiveness of academic institutions. The authors discuss the introduction of managerial approaches of university governance and the effects on the challenges and threats to treat universities like private for-profit businesses. The book is valuable reading for researchers and managers in the field of university governance.